2015
DOI: 10.1016/j.ynstr.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Resilience to the effects of social stress: Evidence from clinical and preclinical studies on the role of coping strategies

Abstract: The most common form of stress encountered by people stems from one’s social environment and is perceived as more intense than other types of stressors. One feature that may be related to differential resilience or vulnerability to stress is the type of strategy used to cope with the stressor, either active or passive coping. This review focuses on models of social stress in which individual differences in coping strategies produce resilience or vulnerability to the effects of stress. Neurobiological mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
90
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(106 citation statements)
references
References 159 publications
3
90
0
2
Order By: Relevance
“…In addition, the results of the direct effects show that the association between general stress and intrinsic/extrinsic motivation for students from low‐tracking schools are solely significant on the within‐level, whereas these associations for students from high‐tracking schools are significant on the between‐level. This supports the assumption that students from low‐tracking schools are more resilient to social stress through more effective coping strategies (Wood & Bhatnagar, ) that could be examined in future studies.…”
Section: How Classmate Stress Affects An Individual's Quality Of Motisupporting
confidence: 76%
“…In addition, the results of the direct effects show that the association between general stress and intrinsic/extrinsic motivation for students from low‐tracking schools are solely significant on the within‐level, whereas these associations for students from high‐tracking schools are significant on the between‐level. This supports the assumption that students from low‐tracking schools are more resilient to social stress through more effective coping strategies (Wood & Bhatnagar, ) that could be examined in future studies.…”
Section: How Classmate Stress Affects An Individual's Quality Of Motisupporting
confidence: 76%
“…These findings may support the neurotoxicity hypothesis, which proposes that stress‐related increases in glucocorticoids and decreases in neurotrophic factors result in hippocampal volume reductions . In contrast, avoidance coping is associated with passivity or helplessness, which results in increased vulnerability to stress . Thus, avoidance coping strategies may not directly be related to hippocampal function.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies have shown that a reactive emotional coping strategy during social defeat, as measured by a short latency to display submissive postures, predicts vulnerability to subsequent development of anxiety-and depressive-like behavioral responses (25,27,60,61) and that inflammatory factors within the CNS drive the vulnerability to depressive-like behavioral responses in individuals with reactive coping responses (32). Thus, the decreased submissive behaviors in M. vaccae-immunized mice are consistent with a stress-resilient behavioral phenotype.…”
Section: Discussionmentioning
confidence: 76%